Mismatch unemployment in Austria: The role of regional labour markets for skills - René Böheim; Michael Christl (European Commission, Joint Research Centre (JRC), 2021)
During the last decade, the Austrian labour market experienced a substantial outward shift of the Beveridge curve - the relationship between the unemployment and the job vacancy rate. Using detailed administrative data on vacancies and registered unemployed by region and skill level, we test which factors caused this shift. We find that the Beveridge curve shifted primarily because mismatch increased substantially. Looking on the regional and skill dimension of mismatch unemployment, we find a substantial increase of mismatch unemployment for manual routine tasks as well as for the region of Vienna.
Keywords: J21; J64; 330; Beveridge curve; unemployment; matching efficiency